Hubungan Konformitas dengan Kepatuhan Santri terhadap Peraturan Pondok Pesantren al-Fath Kota Kediri - Azmi, M. Ulul; Ulla, Fasikhatul; Islam, Muhammad Thoriqul; Mushaffa, Arju; Junaris, Imam; Angrheini, Naal Hira' (Al Asma: Journal of Islamic Education, 2025)
This study aims to analyze the relationship between conformity and compliance with regulations among students at the Al-Fath Islamic Boarding School in Kediri City. Islamic boarding schools, as Islamic educational institutions, emphasize cognitive aspects and foster attitudes, behaviour, and discipline through strict rules. Students' compliance with regulations is influenced by internal and external factors, one of which is conformity, namely the tendency to adjust to group norms. The method used in this study is quantitative with a positivist approach, with a population of 150 students. The sample used was 30 respondents because it was less than 1000, so it used a margin of error of 5%. Data collection used random sampling techniques, questionnaire instruments, and SPSS analysis. The results of the study showed: (1) student compliance was in the moderate category (34.7% or 52 respondents), (2) the level of conformity was also moderate (37.3% or 56 respondents), and (3) the correlation value was -0.319 with a significance of 0.00 <0.05. Thus, a significant negative relationship exists between conformity and students' compliance with regulations at the Al-Fath Islamic Boarding School in Kediri City. The Islamic boarding school leadership can provide facilities in the form of community activities to foster harmony between individuals and groups, create discussion spaces to provide a transparent understanding of the rules to the students, and develop mentoring programs to help students understand and adapt to the environment and rules established by the Islamic boarding school.